Carbon emissions and subjective well-being in Blue Zone Ikaria and Athens, Greece - Radke, Jade; Argentopoulos, Stella; Zhao, Jiaying (Frontiers in Climate, 2025)
Reducing carbon emissions has become largely synonymous with personal sacrifice that can decrease subjective well-being (i.e., happiness, life satisfaction). However, a growing body of research suggests that pro-environmental behavior is positively associated with subjective well-being. To further examine this relationship, this exploratory study examined individual carbon emissions and subjective well-being in Blue Zone Ikaria, Greece, using Athens as a comparison site. Structured interviews and questionnaires with 46 participants (22 in Ikaria, 24 in Athens) revealed that Icarian participants reported higher mental well-being and lower carbon emissions from air travel and clothing consumption than Athenian participants. Icarian participants were also more likely to grow their own food and identify as part of a tight-knit community. These findings suggest that community-focused lifestyles may promote mental well-being while reducing carbon emissions. Future research with larger, more representative samples and objective emissions data is needed to further explore this relationship in Ikaria and other non-WEIRD (Western, Educated, Industrialized, Rich, Democratic) societies.